2017
DOI: 10.1038/srep46444
|View full text |Cite
|
Sign up to set email alerts
|

Cortistatin reduces atherosclerosis in hyperlipidemic ApoE-deficient mice and the formation of foam cells

Abstract: Atherosclerosis is a chronic inflammatory cardiovascular disease that is responsible of high mortality worldwide. Evidence indicates that maladaptive autoimmune responses in the arterial wall play critical roles in the process of atherosclerosis. Cortistatin is a neuropeptide expressed in the vascular system and atherosclerotic plaques that regulates vascular calcification and neointimal formation, and inhibits inflammation in different experimental models of autoimmune diseases. Its role in inflammatory cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Cortistatin can exert manifold biological effects, such as promoting sleep, relieving pain, inhibiting inflammation, inducing immune tolerance and regulating endocrine metabolism, in multiple tissues and cell types. Our study and those of others have revealed CST as a new cardiovascular protective peptide that can reduce myocardial injury induced by sepsis, decrease myocardial fibrosis, inhibit neovascularization and the migration and proliferation of vascular smooth muscle cells (VSMCs), decrease the formation of foam cells and atherosclerosis, and alleviate experimental autoimmune myocarditis . Moreover, our previous study has indicated that CST can attenuate VC in rats .…”
Section: Introductionsupporting
confidence: 54%
“…Cortistatin can exert manifold biological effects, such as promoting sleep, relieving pain, inhibiting inflammation, inducing immune tolerance and regulating endocrine metabolism, in multiple tissues and cell types. Our study and those of others have revealed CST as a new cardiovascular protective peptide that can reduce myocardial injury induced by sepsis, decrease myocardial fibrosis, inhibit neovascularization and the migration and proliferation of vascular smooth muscle cells (VSMCs), decrease the formation of foam cells and atherosclerosis, and alleviate experimental autoimmune myocarditis . Moreover, our previous study has indicated that CST can attenuate VC in rats .…”
Section: Introductionsupporting
confidence: 54%
“…On the basis of these findings, one may theorize a protective role for CST in the adaptive response of the RPE exposed to UV-A radiation. Hypothesis is also supported by several literature evidence: i) apoptotic events induced by UV-A radiation coincide temporally with the overexpression of CST observed in our experimental model (17); ii) CST retinal levels are inversely associated with apoptosis and degree of glial activation, two of the characteristics of retinal neurodegeneration (12); iii) CST protects the rat retina against the blockade of oxidative phosphorylation and glycolysis in vitro (14) and iv) CST shows antiangiogenic, neuroprotective, antioxidant, anti-apoptotic and anti-inflammatory properties, in different biological systems (9,19,20). However, further studies will be necessary because we cannot completely exclude that CST overexpression in our study is rather associated with the beginning and support of the apoptosis and necrosis observed in RPE after exposure to UV-A radiation.…”
Section: Discussionmentioning
confidence: 85%
“…Vascular calcification is not the only cardiovascular pathology that cortistatin is able to limit. In a recent study by Delgado‐Maroto et al, treatment of hyperlipidemic ApoE‐deficient mice with cortistatin had a significant beneficial effect in preventing the development of atherosclerotic plaques in the heart, carotid artery and aorta. Although a different model of vascular calcification, Delgado‐Maroto et al demonstrated that cortistatin downregulated the vascular inflammatory and T‐cell‐mediated response, reducing the ability of endothelial cells to recruit monocytes and atherogenic T cells into the plaque, and reducing the formation of foam cells (by enhancing cholesterol efflux from macrophages).…”
mentioning
confidence: 97%
“…In a recent study by Delgado‐Maroto et al, treatment of hyperlipidemic ApoE‐deficient mice with cortistatin had a significant beneficial effect in preventing the development of atherosclerotic plaques in the heart, carotid artery and aorta. Although a different model of vascular calcification, Delgado‐Maroto et al demonstrated that cortistatin downregulated the vascular inflammatory and T‐cell‐mediated response, reducing the ability of endothelial cells to recruit monocytes and atherogenic T cells into the plaque, and reducing the formation of foam cells (by enhancing cholesterol efflux from macrophages). Of note, however, is that in both the study by Liu examining arteriosclerotic mechanisms, and the work of Delgado‐Maroto examining atherosclerotic lesions, treatment regimens were initiated in acute onset animal models very early in the course of disease establishment.…”
mentioning
confidence: 97%
See 1 more Smart Citation